KARAKTERISTIK MAHASISWA DAN KEPUTUSAN PEMBELIANNYA PADA MAKANAN SEHAT DAN HALAL - Rasmikayati, Elly; Wiyono, Sulistyodewi Nur; Saefudin, Bobby Rachmat (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
ABSTRACTToday many types of modern food have sprung up, but consumers must be careful in choosing whether the food is healthy and halal. The purpose of this research is to describe the characteristics and buying behavior of students towards healthy and halal food. The research method used is survey and data analysis technique is descriptive statistics. The results of this study found that the majority of respondents were women with 59%, while the most income was in the range of 1-2 million/month with 45%. In this study, in general, respondents were quite careful in choosing healthy and halal food products. The results of other behaviors in reading food labels to check for ingredients that are hazardous to health in food, show differences in the number of respondents, namely the number of male respondents is less than the number of female respondents. While other behaviors, namely the behavior of ensuring that there is a halal label on processed food before buying it, the behavior of choosing places to eat that are labeled healthy food, and the behavior of choosing places to eat that are labeled halal, did not show a significant difference in the number of respondents.